Uma metrópole em transição: reestruturação produtiva e a emergência do turismo na RM de Fortaleza-CE - Montenegro Júnior, Ignácio Ribeiro Pessoa (2012)
The objective of this research is to shed light on the debate about recent socio-spatial transformations in Brazilian cities. One can observe in these transformations market processes and niches linked to real-estate products that participate as the causes for the urban dissolution in contemporary large cities, characterized by territorial fragmentation and social segregation. While focusing on those real-estate products that are linked to tourism, we have aimed to understand the process by way of which the articulation of such new form of social production of space, based on an emerging scenario created by social agents, takes place. Such agents are seen as the subjects who bring forth innovative urban practices though intrinsically committed to the logic of quick increase of capital. Such focus can be justified for provoking a discussion about the concepts of occupation pattern and spatial structuring, as an attempt to understand the new role played by real-estate agents involved in tourism. In the first chapter we approach the theoretical discussion on the production of contemporary cities in a re-structuring context, analyzing the fundamentals of production and appropriation of the contemporary urban space. As our point of departure, we took over the concept of social space and its production as a strategy towards the accumulation of capital, emphasizing the role played by the market and the State in the spatial organization of production. Then we discussed both the metropolitan transitional issue and the urban dissolution of contemporary cities, by using the concept of a restructuring standpoint associated with the concept of globalization, emphasizing the new pattern of city as well as the new spatial configuration. In the second chapter we carry out the first approximation to the central issue, analyzing the coastal urbanization in the context of the metropolitan re-structuring of Fortaleza. Thus, we examined the detailed features of the Coastal Areas of Ceará, the ‘occupational process’ of those areas and the consolidation of Fortaleza as a Capital City, by emphasizing, in detail, the process as it gradually became a metropolis. For that reason, we started from an analysis that comprehends from the belated industrialization of the Northeast of Brazil to the productive and socio-territorial re-structuring of modern Ceará in order to emphasize the emergency of tourism in its relation to the production of a new urban coastal space. In the third chapter we treated the central issue of both the metropolitan restructuring and the emerging need for tourism, focusing on the participation of real-estate agents as in the case of Aquiraz. Such a choice is due to the fact that that coastal line reveals more clearly the issue under analysis, creating conclusive elements capable of consolidating our final considerations. Thus it was possible to say in conclusion that ‘the action of those real-estate agents respond to the re-organization of a new process of production of space for tourism, in the face of the need to incorporate new territories into the logic of capital growth’.